PENGARUH POSITIVISME DALAM PERKEMBANGAN ILMU HUKUM DAN PEMBANGUNAN HUKUM INDONESIA - Wahyuni, Sri (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
This article discusses about the positivism influence to jurisprudence and law development, especially in Indonesia, and the analysis of the strength and the weakness of the positivism influence. Through the positivism which was introduced by August Comte, the rational and empiric truth and the standard of natural sciences were used also in the social sciences, law and jurisprudence. The concept of legal positivism is the proof of the positivism influence in law and jurisprudence. Legal positivism develops as the written law which is formulated by the legitimated state organ which has the power and souveregnity. It is separated from the moral and the right and wrong values. There were many scholars who use the positivism in their legal opinion, namely Hart, Hans Kelsen and John Austin. The concept of legal positivism in Indonesia also follows the legal positivism opinion, which seen in many aspect such as the written law, law unification, and legislation.